Migraines - HSTN ( Health & Sciences Television Network) (Carrollton : HSTN, 2000)
This program examines the migraine -- a particularly excruciating and incapacitating type of headache. It profiles studies on the migraine, highlighting advances in neuroimaging that have pinpointed affected areas in the brain. It also outlines general principles of treatment and nursing management of migraine sufferers
Keywords: Migraine -- nursing; Nursing